The dynamic role of mRNA m6A methylation in Arabidopsis thaliana and Solanum lycopersicum - Chak, Samuel Erwin Seng Chung (2024)
The N6-methyladenosine (m6A) modification in mRNA is the most abundant internal chemical modification found in eukaryotic mRNA, and it is also present in a variety of bacteria and RNA viruses. This modification is highly conserved across most eukaryotic organisms and their components and interactions is becoming a popular interest in the field of RNA research. The addition of m6A in mRNA is catalysed by the methyltransferase complex termed “Writer,” which is a multi-protein subunit complex consisting of various proteins. The recognition modification of m6A is termed recognised by the “Reader,” proteins, while the removal of this modification is facilitated by proteins termed the the “Erasers.” We have identified two Arabidopsis thaliana suppressor lines from EMS mutagenesis which revert fip37-4 (SALK insertion line), a knockdown of FIP37 (Writer protein) low methylation phenotype to Wild type (WT) like phenotype. Bulk segregant analysis and RNA-Sequencing have identified candidate genes for both lines which could explain the reversion back to WT-like phenotype. This study also explores the reader proteins in Solanum lycopersicum, as we have identified single and double knockout of each of the four YTHDFs in tomato. Single knockout of each of the four YTHDFs reader proteins in S. lycopersicum did not result in embryo lethality. Furthermore, we have generated an inducible RNAi knockdown line targeting the MTA gene in S. lycopersicum, which resulted in an increase in the number of lateral branches along with an increase in MTA transcript abundance upon induction and activation of the hpRNAi construct. This work provides an avenue to produce knockdown or knockout lines for the writer protein MTA and reader proteins consisting of YTHDFs, enabling a better understanding of how m6A methylation is deposited and recognised.